TENDÊNCIAS DA POLÍTICA DE SAÚDE NO BRASIL E OS DESAFIOS PARA A SOLIDIFICAÇÃO DO SISTEMA ÚNICO DE SAÚDE - Olívia Vieira da Silva; Marcelo Medeiros; Ivete Santos Barreto (Universidade Federal de Goias, 1999)
TENDENCIES OF THE HEALTH POLICY IN BRAZIL AND THE CHALLENGES FOR THE ESTABLISHMENT OF UNIQUE SYSTEM OF HEALTH SERVICES From all those years of SUS (Unique Health Service System) implantation, it is possible to evidence the negligence on the services and activities of the public of health system. The reality that we lived is almost of absolute precarious conditions in the attendance to the health of the collectivity. This study aim to identify aspects that can contribute to the reflection about tendencies of the Brazilian public health policy, stimulating the discussion and nurses participation while citizen and of Nursing in the process of implantation of SUS. The results points that although our Constitutional conquest, of health as a right of all the citizens and duty of the State, be guaranteed by social and economical politics, the health is the most included because, through SUS the universal access is guaranteed, with integral and free attendance, we lived the implantation difficulties and implementation of this system the clear project of it dismounts captained by the Federal Government, with your neoliberal politics that determines the political process and of financing in direction diametrically opposite. Therefore, the promise of a health with more resources to the population less favoured bed medium terms in direction to a poor health to assist poor. All considering these aspects, we placed then, the challenge of to publish and to reproduce the experiences from where being believed in SUS and investing in the quality of attendance to the population, they settled down partnerships between City halls and Municipal Council of Health and they did with that the Model extolled by our Constitution grows with success.